Representações, valores e cotidiano em narrativas de participantes do ProJovem Adolescente - Mendes, Amanda Jacinto (2013)
This research aims to investigate the stories of teenagers who participate in the Program Socio Projovem Teenager, confronting the narratives of adolescents who participate in the program with the discourses of social agents, which have the goal of reducing social vulnerability of the country being referred by the municipal social assistance units called Reference Center for Social Assistance - CRAS. The research, kind of ethnographic, was conducted in two CRAS in Rondonópolis city, which were observed in the daily application of Adolescent Projovem; were made in oral interviews with eleven teenagers about their experience in the program, interviews with five professionals who work directly with teens; analysis documentary, having as object the material prepared by the Federal Government to direct the operation of the program. The analysis was guided by the concepts of polyphony speech and verbal Extra context Bakhtin and the references and definitions of transactions / negotiations Bruner. The two authors define language as an essential component for human relations and present a dialectical exchanges through the same. The analysis sought to highlight the narratives of teenagers in dialogue with other materials collected on the program, allowing to establish the mechanisms and strategies of the program to work with the emancipation and autonomy of individuals served, as well as the ways in which teenagers appropriated the program and its purpose. Representations of adolescence as a time of life and their role in building the country, which are present in the dialogues undertaken with different instruments, allowing you to build departures and approaches the teen program user with the public policy of the country, highlighting the role of family as a value and the possibility of social mobility from the frequency in Projovem. Interviews with educators oppose the program the lines of teens and confirm that the intentions of the state for the future of adolescence in social vulnerability in the country are not always in accordance with the interests of those who are enrolled in the program. The program sets up as a disciplinary action that does not bother to listen to teens and assumes a conception of adolescence as an investment for the future. Teenagers are not displayed by the program and by social agents as subjects of rights itself, but as an opportunity for social and economic development.